Diabetic myopathy: impact of diabetes mellitus on skeletal muscle progenitor cells - D'Souza, Donna M.; Al-Sajee, Dhuha; Hawke, Thomas J. (Frontiers in Physiology, 2013)
Diabetes mellitus is defined as a group of metabolic diseases that are associated with the presence of a hyperglycemic state due to impairments in insulin function. While the development of each form of diabetes (Type 1 or Type 2) drastically differs, resultant pathologies often overlap. In each diabetic condition a failure to maintain healthy muscle is often observed, and is termed diabetic myopathy. This significant, but often overlooked, complication is believed to contribute to the progression of additional diabetic pathologies due to the vital importance of skeletal muscle for our physical and metabolic well-being. While studies have investigated the link between changes to skeletal muscle metabolic health following diabetes mellitus onset (particularly Type 2 diabetes mellitus), few have examined the negative impact of diabetes mellitus on the growth and reparative capacities of skeletal muscle that often coincides with disease development. Importantly, evidence is accumulating that the muscle progenitor cell population (particularly the muscle satellite cell population) is also negatively affected by the diabetic environment, and as such, likely contributes to the declining skeletal muscle health observed in diabetes mellitus. In this review, we summarize the current knowledge surrounding the influence of diabetes mellitus on skeletal muscle growth and repair, with a particular emphasis on the impact of diabetes mellitus on the progenitor cell population of skeletal muscle.